Feverish fictions: William T. Vollmann and American literary history after postmodernism. Issue 2 (7th February 2019) - Coffman, Christopher K.
ABSTRACT: The rise of the New Sincerity in contemporary American fiction has largely been read on terms provided by a handful of early proponents. This article contends that more complex formulations of the notion are necessary if it is to remain useful as a descriptor for important qualities of recent texts. Among issues in need of greater attention are the implications of the New Sincerity for historical awareness, a topic I pursue via consideration of William T. Vollmann's grappling with literary history. I argue that Vollmann's works offer more than the pastiche that allegedly defined historical consciousness in postmodernist fiction. His intertextual engagements with Edgar Allan Poe are especially valuable for modelling some of the ways recent fictions bypass postmodernist ahistoricism in favour of connections to a usable past, and, especially, a usable literary tradition. Readings of Vollmann's 'The Grave of Lost Stories' (in several editions) and 'The Cemetery of the World' show how he employs research in the textual archive as a figuration of relations to the past that can serve the ends of renewal and recovery.